Co-occurrence of EIF1AX, SF3B1, or BAP1 variants in uveal melanomas: A case series and review - Henry C. Skrehot; Amer F. Alsoudi; Amy C. Schefler (American Journal of Ophthalmology Case Reports)
Purpose: The purpose of this study is to present a case series of patients with co-occurrence of either BRCA1 associated protein-1 (BAP1), eukaryotic translation initiation factor 1A, X-chromosomal (EIF1AX), or splicing factor 3B subunit 1 (SF3B1) in the detection and treatment of a uveal melanoma (UM) prior to the development of metastatic disease. Observations: This is a retrospective case series of ten patients with UM demonstrating co-occurrence of either BAP1, EIF1AX, or SF3B1 variants treated at a single ocular oncology clinic by a senior ocular oncologist between 2020 and 2024. Charts were reviewed and data on medical history, demographics, tumor characteristics, genetic testing, follow up, as well as fundus photo and B-scan ocular ultrasound were collected. The average age of the patients was 58.5 years old. The mean length of follow up was 18.2 months. Four patients had guanosine nucleotide-binding protein alpha-11 (GNA11) variants and six had guanosine nucleotide-binding protein Q (GNAQ) variants. Four patients had germline BAP1 variants. Four patients had a combination of EIF1AX and BAP1 variants. Three patients had a combination of EIF1AX and SF3B1 variants. Three patients had a combination of SF3B1 and BAP1 variants. Eight UM were gene expression profile (GEP) Class 1A and two UM were GEP Class 1B. Seven UM were preferentially expressed antigen in melanoma (PRAME) negative and three UM were PRAME positive. All patients had cytologic confirmation of the diagnosis of UM: seven had cytology results of spindle cells and three had results of mixed spindle and epithelioid cells. All patients were treated with Iodine-125 (I-125) plaque brachytherapy. Conclusions and importance: We present a case series of patients with the co-occurrence of EIF1AX, SF3B1, or BAP1. With distinct genomic aberrations, transcriptional features, and clinical outcomes, EIF1AX, SF3B1, and BAP1 are thought to be mutually exclusive. The present case series demonstrates rare exceptions to this general pattern and speculates on the early molecular steps of UM which may lead to these rare mutation combinations.